RELEGIUSITAS BANTEN SIAP SAJI DI TENGAH TRANSFORMASI BUDAYA MASYARAKAT BALI - I Wayan Suharta (Jurnal Penjaminan Mutu, 2022)
In Bali, most of the cycles of religious life are controlled by ceremonial activities of a religious nature. Ceremonial activities are not only a necessity but also a necessity. It makes sense if later the Hindus in Bali became ceremonial people, they worshiped themselves, others, including nature and the environment. As a result of their very limited abilities, Hindus use facilities in the form of banten as a form of offering. Religious activities that use offerings are quite dense. The choice of "ready to serve offerings" is no longer taboo, it even tends to become a habit. The phenomenon of using ready-to-eat offerings is a representation of proof that Hindus, in terms of their corpses, almost never leave the smell and feel of a colossal-style ritual. As an inseparable part of modern society, Hindus in Bali inevitably fall into the trap of a global society's lifestyle which is full of materialism, capitalism, and consumerism. Their daily life is so busy competing for a living, so the availability of time for the business of making offerings is very limited. By earning money from the work, he takes a practical way by buying the ready-to-serve offerings.